Peran Kepala Sekolah sebagai Supervisor dalam Optimalisasi Kompetensi Pedagogik Guru di SMPN 2 Kota Lhokseumawe - Nurasiah Nurasiah (Medan Resource Center, 2022)
The purpose of this study is: to describe the role of the principal as a supervisor in optimizing the pedagogic competence of teachers at SMPN 2 Lhokseumawe. This study uses a type of qualitative research with a field study approach, where the source of data is obtained from interviews with school principals, Curriculum Representatives and teachers, Furthermore, data collection techniques used documentation, observation and interview techniques which were then processed using reduction, display and data verification techniques. Based on the results of the study it was found that: The role of the principal as a supervisor in optimizing the pedagogical competence of teachers at SMPN 2 Lhokseumawe that is true, the principal has played a role as a supervisor, this is proven one way or another by the way the principal as a supervisor has included teachers in training activities carried out by the central institution through the Education Quality Assurance Agency and Education Personnel carried out by the Provincial Education Office through the UPTD The Center for Teacher Quality Development both in the Province and in the District/City, in addition to that the school principal as a supervisor has sent teachers to take part in activities carried out by the Subject Teacher Consultation forum (MGMP).